2009
DOI: 10.1104/pp.109.142729
|View full text |Cite
|
Sign up to set email alerts
|

Unique Features of Plant Cleavage and Polyadenylation Specificity Factor Revealed by Proteomic Studies

Abstract: Cleavage and polyadenylation of precursor mRNA is an essential process for mRNA maturation. Among the 15 to 20 protein factors required for this process, a subgroup of proteins is needed for both cleavage and polyadenylation in plants and animals. This subgroup of proteins is known as the cleavage and polyadenylation specificity factor (CPSF). To explore the in vivo structural features of plant CPSF, we used tandem affinity purification methods to isolate the interacting protein complexes for each component of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 50 publications
(91 reference statements)
0
27
0
Order By: Relevance
“…In plants, a similar set of poly(A) factors were identified, albeit with some differences in the number of encoding genes and domain structures (Hunt et al 2008. Genetic and biochemical analysis of these factors also revealed similar, but distinct, and sometimes unique, functions to their animal counterparts (Zhao et al 2009(Zhao et al , 2011Thomas et al 2012;Xing et al 2013;Liu et al 2014).…”
mentioning
confidence: 96%
“…In plants, a similar set of poly(A) factors were identified, albeit with some differences in the number of encoding genes and domain structures (Hunt et al 2008. Genetic and biochemical analysis of these factors also revealed similar, but distinct, and sometimes unique, functions to their animal counterparts (Zhao et al 2009(Zhao et al , 2011Thomas et al 2012;Xing et al 2013;Liu et al 2014).…”
mentioning
confidence: 96%
“…The endonuclease activity is attributable to the C-terminal zinc finger motif. Beyond these biochemical activities, the Arabidopsis CPSF30 sits at the center of a hub of protein-protein interactions involving other CPSF subunits as well as other components of the polyadenylation complex Zhao et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Future directions should include the identification of the plant cleavage/ polyadenylation factors that are responsible for the activities, and the roles of those potential factors revealed through bioinformatic and genetic studies, as confirmed by protein-protein interactions (Xu et al, 2006;Hunt et al, 2008;Xing et al, 2008aXing et al, , 2008bZhao et al, 2009). Several approaches can be employed to identify the plant polyadenylation factors through this type of biochemical assay.…”
Section: Discussionmentioning
confidence: 99%
“…While studying the proteomics of plant polyadenylation factors, we overexpressed Arabidopsis CPSF73-I (for CPSF 73-kD subunit-I; At1g61010) using a tandem affinity purification tagging approach and isolated the protein complexes formed with it (Zhao et al, 2009). Arabidopsis CPSF73-I is a homolog of mammalian CPSF73 that was shown to be the endonuclease that plays a direct role in the cleavage step of pre-mRNA 3#-end formation (Dominski et al, 2005;Mandel et al, 2006).…”
Section: Establishment Of a Plant In Vitro Pre-mrna Cleavage System Umentioning
confidence: 99%
See 1 more Smart Citation